The fort eaudiobook - Korman, Gordon (Recorded Books, Inc., 2022)
The morning after Hurricane Leo rips through their town, Evan, Jason, Mitchell, and C.J. find a total mess outside, with downed branches and uprooted trees everywhere. They know they should stay indoors—but they want to go exploring, even if it means having a new kid, Ricky, tag along. Ricky's the first one to discover a strange trapdoor in the middle of the woods—the door to an old bomb shelter, unearthed by the hurricane. Inside, the boys find a completely intact underground lair, with electricity, food, and even a TV. The boys vow to keep the place a secret. It's theirs now. But some secrets are hard to keep ... especially when adults and older kids are closing in. And what started out as a fun place to escape soon becomes a serious refuge for one of the boys, who is trying to avoid his abusive stepfather. The Fort has become the safest place they have—will they be able to protect it?